Pense nas aventuras da água - Colosso, Cristiane Otília; Lima , Eliene Xavier de; Bento , Miriam Furtado; Schiavinato , Ricardo Leandro; Couto , Silvana Bento de Melo (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf